Coupled Cognitive Changes in Adulthood: A Meta-analysis - Tucker-Drob, Elliot M. (Psychol Bull, 2019)
With advancing age, healthy adults typically exhibit decreases in performance across many different cognitive abilities such as memory, processing speed, spatial ability, and abstract reasoning. However, there are marked individual differences in rates of cognitive decline, with some adults declining steeply and others maintaining high levels of functioning. To move toward a comprehensive understanding of cognitive aging, it is critical to know whether individual differences in longitudinal changes interrelate across different cognitive abilities. We identified 89 effect sizes representing shared variance in longitudinal cognitive change from 22 unique datasets composed of over 30,000 unique individuals, which we meta-analyzed using a series of multilevel meta-regression models. Results indicate that an average of 60% of the variation in cognitive changes is shared across cognitive abilities. Shared variation in changes increased with age, from approximately 45% at age 35 years to approximately 70% at age 85 years. There was a moderate-to-strong correspondence (r = .49, congruence coefficient = .98) between the extent to which a variable indicated general intelligence and the extent to which change in that variable indicated a general factor of aging-related change. Shared variation in changes did not differ substantially across cognitive ability domain classifications. In a sensitivity analysis based on studies that carefully controlled for dementia, shared variation in longitudinal cognitive changes remained at upwards of 60%, and age-related increases in shared variation in cognitive change continued to be evident. These results together provide strong evidence for a general factor of cognitive aging that strengthens with advancing adult age.